Figuring the Chinese film festivalscape: the Pingyao International Film Festival’s cultural and political interplay - Qi Wang; Md Azalanshah Md Syed; Sicheng Liu; Muhamad Shamsul Ibrahim (Cogent Arts & Humanities)
Opened in 2017, the Pingyao International Film Festival has quickly become a signature event in the Chinese film landscape. Co-founded by renowned Chinese director Jia Zhangke and prominent film festival expert Marco Müller, PYIFF distinguishes itself through its unique coordination between private power and government institutions. This study explores the distinct characteristics of PYIFF compared to other Chinese film festivals, focusing on its impact on the film industry in Shanxi Province. Using qualitative research, case studies, and in-depth interviews, this article comprehensively analyses PYIFF’s programming, audience engagement, and political dynamics. It highlights how the festival navigates the complex interplay between official involvement and independent initiative. By employing strategies such as focusing on non-Western films and using alternative terminology to mitigate political risks and censorship issues, PYIFF has managed to maintain a degree of independence while aligning with national policies. The findings underscore PYIFF’s role in promoting Shanxi’s film industry and cultural atmosphere, despite challenges posed by political constraints. This article contributes to the growing body of literature on Chinese film festivals and cultural diplomacy, offering insights into the unique challenges and opportunities faced by festivals operating within politically sensitive contexts.